Case Report: A case of ALS type 6 associated with a FUS gene variant and right limb muscle weakness and atrophy as the initial symptom - Zhan, Xiuping; Xuan, Tingting; Chen, Xiaoyan; He, Jianhang; Ren, Yazhou; Meng, Yue; Chen, Guisheng; Li, Haining (Frontiers in Genetics, 2025)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the progressive degeneration of upper and lower motor neurons. This degeneration results in increasing muscle weakness, ultimately culminating in respiratory failure and death. Mutations in the fused in sarcoma (FUS) gene have been identified as a significant cause of ALS. Here, we present the case of a 40-year-old woman who exhibited right limb muscle weakness and atrophy as her initial symptom. Whole genome sequencing revealed a mutation in the FUS gene, specifically c.1450_1456delinsCCC (p.Tyr484Profs*44), leading to a diagnosis of ALS type 6 (ALS6). The c.1450_1456delinsCCC (p.Tyr484Profs*44) mutation is a frameshift mutation resulting from a non-triplet base deletion in the coding region of the FUS gene. This mutation is novel and has not been previously reported in China or internationally. Furthermore, the onset of muscle weakness and atrophy exclusively in the ipsilateral limb is very rare among ALS patients, and we have found no related reports. This case report aims to enhance medical professionals’ understanding of the complexities associated with ALS caused by FUS gene mutations and the onset of ALS symptoms, thereby facilitating more accurate clinical diagnosis and treatment.